Tracked Changes. Chemical disinfectants and antiseptics. Quantitative suspension test for the evaluation of fungicidal or yeasticidal activity in the medical area. Test method and requirements (phase 2, step 1). (16th November 2022) - British Standards Institution,
No abstract available